(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
Since the late eighties gradual beginswithdrawal of the state from the exercise of anumber of social function. The process of commercializingis the result of globaliza-tion and the pressure exerted by international business. Along with the progressive mar-ketization develops the concept of activating state in whichthe emphasis is on active citizens and take responsibility for their fate, and satisfy the needs of a social nature.